2020
DOI: 10.1678/rheology.48.49
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Test for the Homogeneity of Aqueous Blends of Associative Polymer Network and Entangled Linear Polymer

Abstract: Linear viscoelastic behavior has been examined for the mixtures of a transient network and entangled linear polymers in aqueous solutions. We have found that the aqueous blends of hydrophobically ethoxylated urethane (HEUR) and sodium polyacrylate (PAANa) become transparent solutions and look homogeneous. To examine the molecular level homogeneity of this mixture, we analyze the linear viscoelastic spectra as functions of the volume fraction of PAANa, ϕ P , at fixed HEUR concentrations, especially focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this review, we introduce the recent progress on this field using two model transient networks: hydrophobically ethoxylated modified urethane (HEUR) and Tetra-PEG slime. The former is one of the associative polymers, which has been utilized by many researchers [24][25][26][27][28][29]. The latter is a class of transient networks with regular network structures developed by our group, comprising of the multi-armed prepolymers [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we introduce the recent progress on this field using two model transient networks: hydrophobically ethoxylated modified urethane (HEUR) and Tetra-PEG slime. The former is one of the associative polymers, which has been utilized by many researchers [24][25][26][27][28][29]. The latter is a class of transient networks with regular network structures developed by our group, comprising of the multi-armed prepolymers [30].…”
Section: Introductionmentioning
confidence: 99%
“…Following their work, various models have considered the interplay between polymer-and crosslink dynamics as stickers, including the sticky Rouse model 20,21) , sticky reptation model [21][22][23][24] , and reversible gelation model 25,26) . Alternatively, considerable experimental studies have been conducted to elucidate the viscoelasticity of the transient networks by using thermoresponsive ABA block copolymers [27][28][29][30] , hydrophobically end-capped polymers [31][32][33][34][35][36][37] , ionomers 25,[31][32][33][34][35][36][37][38][39][40] , "slime" [41][42][43] , etc. In addition, some studies reported the use of wormlike (threadlike) micelles, which are also strongly relevant [44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…Because the reversible bond nature differs from the covalent bond, these crosslinks continuously bind and dissociate, where the translational diffusion of the constitutive polymers is permitted. As a result, the transient networks are not solid, but are liquid showing temporal elasticity (viscoelastic liquid) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Because they can slowly dissolve into a solvent and release the entrapped molecules, there have been many applications for drug-delivery carriers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%